A Threefold Interpenetrated Pillared‐Layer Metal–Organic Framework for Selective Separation of C2H2/CH4 and CO2/CH4. Issue 8 (27th April 2016) - Alduhaish, Osamah; Wang, Hailong; Li, Bin; Arman, Hadi D.; Nesterov, Vladimir; Alfooty, Khalid; Chen, Banglin
Abstract: A new threefold interpenetrated pillared‐layer microporous metal–organic framework, [Zn2 (cca)2 (4‐bpdb)] n ⋅ (DMF)2 n (UTSA‐85) (H2 cca=4‐carboxycinnamic acid, 4‐bpdb=1, 4‐bis(4‐pyridyl)‐2, 3‐diaza‐1, 3‐butadiene, and DMF= N, N ‐dimethylformamide), has been designed and generated by the solvothermal reaction of mixed ligands (H2 cca and 4‐bpdb) and Zn(NO3 )2 ⋅ 6 H2 O. Single‐crystal XRD analysis disclosed that discrete paddle‐wheel Zn2 (COO)4 clusters as secondary building units linked the cca ligands to give two‐dimensional layers, which were further pillared by 4‐bpdb ligands to form a threefold interpenetrated pillared‐layer structure. The desolvated framework, UTSA‐85 a, was revealed to exhibit permanent porosity with a BET surface area of 558 m 2  g −1 and a high selectivity of 64 for C2 H2 /CH4 separation at 296 K owing to the microporous (≈5.0 Å) structure and functional azine groups that decorated the pore channels. Abstract : Trapped wind : A new threefold interpenetrated pillared‐layer microporous metal–organic framework, [Zn2 (cca)2 ‐(4‐bpdb)] n ⋅ (DMF)2 n (UTSA‐85) (H2 cca= 4‐carboxycinnamic acid, 4‐bpdb=1, 4‐bis(4‐pyridyl)‐2, 3‐diaza‐1, 3‐butadiene, and DMF= N, N ‐dimethylformamide), is described. The desolvated framework, UTSA‐85 a, exhibits high selectivity for C2 H2 /CH4 separation as a result of the microporous structure and functional azine‐groups decorating the pore channels (see figure).